Nicorandil reduces the antimicrobial effectiveness of polymyxin E against Klebsiella pneumoniae by decreasing reactive oxygen species accumulation - Zhu, Rongqing; Luo, Fangxin; Yuan, Chenxi; Fang, Ziqian; Guo, Yaqin; Meng, Bao; Zhao, Dongmei; Liu, Yanyan; Yang, Yi; Li, Yasheng; Li, Jiabin; Yu, Liang (Frontiers in Cellular and Infection Microbiology, 2025)
Nitric oxide (NO) plays a crucial role in bacterial physiology and survival, particularly in relation to antibiotic resistance. The protective role of NO against antibiotics is intricate, and the potential antagonistic interactions between NO donors and polymyxin E remain largely unexplored. This study aimed to evaluate the antagonistic effects of nicorandil, a NO donor, on the bactericidal activity of polymyxin E against Klebsiella pneumoniae. Methods: Thirty clinical strains were identified as multidrug-resistant K. pneumoniae using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). The antimicrobial efficacy of polymyxin E combined with nicorandil against K. pneumoniae was evaluated through in vitro rapid killing assays and growth curve analyses, and in vivo using a murine pulmonary infection model and a Galleria mellonella larvae infection model. The release of NO by nicorandil was confirmed via reactive nitrogen species (RNS) assays. The impact of NO on oxidative stress responses induced by polymyxin E was evaluated using reactive oxygen species (ROS) assays and RT-qPCR. Results: Nicorandil counteracted the bactericidal effects of polymyxin E in 16 out of 30 clinical isolates of K. pneumoniae. Notably, the most pronounced effects were observed in the K. pneumoniae strain GN 191035. In this context, the release of NO from nicorandil conferred protection to the bacteria against oxidative stress by reducing ROS, as demonstrated by a murine model of pulmonary infection and a Galleria mellonella larvae infection model. Conclusions: Our study further elucidated that nicorandil treatment mitigates the bactericidal efficacy of polymyxin E against K. pneumoniae. These findings highlight the significant risk of increased bacterial infections associated with the concurrent administration of nicorandil and polymyxin E.